The role of Information technology (IT) in coping with the challenges of Agriculture sector - Zayan, Sahar (2019)
As part of the IFPRI Egypt Seminar in partnership with the World Bank, IFPRI Egyprt seminar “Innovations for Agricultural Development in Egypt”.